Application of the Behavioral Architecture Theme in the Design of the Class IIA Women's Special Penitentiary Building in Banda Aceh - Dinda Meidina Anjani; Mirza Mirza; Khairul Huda (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2022)
Women's Correctional Institution is a building where people who have been sentenced to confinement, where the sanctions given are more of a training nature, in this case the occupants are women over 18 years. Generally, Correctional Institutions are impressive and terrible with being surrounded by high walls and barbed wire on top which depicts prison conditions in the Dutch era. However, this Women's Correctional Institution will implement a correctional system which is an order regarding directions and boundaries as well as the method of fostering prisoners based on Pancasila which is carried out in an integrated manner between the coaches, those who are fostered and the community by applying the behavioral architecture theme. Behavioral architecture applies knowledge of designing a building or behavior based on human behavior or behavior in it.